Despliegue de caracteres - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
The activities on character deployment involve the recombination or use of desirable characters (e.g., level of resistance to diseases and insect pests, tolerance to drought, ability to fix atmospheric N) in commercial cv., according to the needs of the particular production region for which the material is intended. Those activities include the distribution of adaptation nurseries, release of new cv., analysis of the different production problems, and germplasm improvement strategies. Research on character deployment done for Central America, Mexico (coastal and highlands), the Caribbean, Argentina, Brazil, West Asia, North and Eastern Africa, and Andean region is summarized. (CIAT)